Realizing virtual research environments for the agri‐food community: The AGINFRA PLUS experience. (25th November 2020) - Assante, Massimiliano; Boizet, Alice; Candela, Leonardo; Castelli, Donatella; Cirillo, Roberto; Coro, Gianpaolo; Fernández, Enol; Filter, Matthias; Frosini, Luca; Georgiev, Teodor; Kakaletris, George; Katsivelis, Panagis; et al.
Abstract: The enhancements in IT solutions and the open science movement are injecting changes in the practices dealing with data collection, collation, processing, analytics, and publishing in all the domains, including agri‐food. However, in implementing these changes one of the major issues faced by the agri‐food researchers is the fragmentation of the "assets" to be exploited when performing research tasks, for example, data of interest are heterogeneous and scattered across several repositories, the tools modelers rely on are diverse and often make use of limited computing capacity, the publishing practices are various and rarely aim at making available the "whole story" including datasets, processes, and results. This paper presents the AGINFRA PLUS endeavor to overcome these limitations by providing researchers in three designated communities with Virtual Research Environments facilitating the use of the "assets" of interest and promote collaboration.